Whole-Genome Analysis Deciphers Population Structure and Genetic Introgression Among Bovine Species - Li, Rong; Chen, Shanyuan; Li, Chunqing; Xiao, Heng; Costa, Vânia; Bhuiyan, Mohammad Shamsul Alam; Baig, Mumtaz; Beja-Pereira, Albano (Frontiers in Genetics, 2022)
It is known that throughout history and presently taurine (Bos taurus) and indicine/zebu (Bos indicus) cattle were crossed with other bovine species (e.g. gayal, gaur, banteng, yak, wisent and bison). Information on the role of interspecific hybridization to facilitate faster adaptation of the newly arrived domestic species to new environments is poorly known. Herein, we collected 266 samples of bovine species of taurine, zebu, yak and gaur from West Europe, Southwest China, Indian subcontinent and Southeast Asia to conduct the principal component analysis (PCA), admixture, gene flow and selection signature analyses by using SNPs distributed across the bovine autosomes. The results showed that the genetic relationships between zebu, yak and gaur minored their geographical origins. Three ancestral components of the European taurine, East Asian taurine and Indian zebu were found in domestic cattle, and the bidirectional genetic introgression between Diqing cattle and Zhongdian yak was also detected. Simultaneously, the introgressed genes from Zhongdian yak to Diqing cattle were mainly enriched with immune-related pathways and the ENPEP, FLT1 and PIK3CA genes related to the adaptation of high-altitude hypoxia were detected. Additionally, we found the genetic components of Zhongdian yak had introgressed into Tibetan cattle. The 30 selected genes were detected in Tibetan cattle, which were significantly enriched in chemokine signaling pathway. Interestingly, some genes (CDC42, SLC39A2 and EPAS1) associated with hypoxia response were discovered, in which CDC42 and SLC39A2 played important roles in angiogenesis and erythropoiesis, and heart function, respectively. This result showed that genetic introgression was one of the important ways for the environmental adaptation of domestic cattle.